Incidence and risk factors for restenosis, and its impact on blood pressure control after percutaneous transluminal renal angioplasty in hypertensive patients with renal artery stenosis. Issue 7 (July 2016) - Iwashima, Yoshio; Fukuda, Tetsuya; Yoshihara, Fumiki; Kusunoki, Hiroshi; Kishida, Masatsugu; Hayashi, Shin-ichiro; Nakamura, Satoko; Kamide, Kei; Horio, Takeshi; Kawano, Yuhei
Abstract : Objective: Percutaneous transluminal renal angioplasty (PTA) is one of the standard treatments for renal artery stenosis (RAS). We investigated the frequency and risk factors for restenosis, and its impact on blood pressure (BP) control. Methods: A total of 175 hypertensive patients with RAS [mean age 60 years; 34% women; 30.3% fibromuscular dysplasia (FMD)] with 207 treated renal arteries were included and followed for more than 1 year without reangioplasty. Diagnosis of restenosis was based on duplex ultrasonographic findings, and data including BP and antihypertensive medication were collected consecutively. Results: During follow-up (mean, 5.1 years), 56 patients (32.0%) developed restenosis. In multivariate Cox regression analysis, FMD was an independent predictor of restenosis (hazard ratio 2.65, P < 0.05). When divided into two groups based on FMD or atherosclerotic RAS (ARAS), the presence of previous cardiovascular disease (hazard ratio 2.84) as well as severe RAS (≥90%) (hazard ratio 3.95) in ARAS were independent predictors of restenosis ( P < 0.05, respectively). At 1 year after PTA, 35 patients (20.0%) had developed restenosis. When divided into four groups on the basis of FMD or ARAS, and the absence/presence of restenosis at 1 year, the number of antihypertensive drugs was significantly lower in both FMD and ARAS patients without restenosis ( P < 0.01, respectively); however, a significant difference in decrease in SBP (−31 ± 19 vs. −12 ± 25 mmHg, P < 0.05) as well as cure of hypertension (36.4 vs. 5.0%, P < 0.01) between the absence/presence of restenosis was found only in FMD patients. Conclusion: The frequency of restenosis after renal PTA is significant, and the presence of restenosis diminishes the benefit of its treatment, especially for FMD.